PENINGKATAN KEMAMPUAN KONEKASI MATEMATIS DAN BERPIKIR KREATIF SISWA MELALUI PEMBELAJARAN OPEN ENDED DI SMP MUHAMMADIYAH 03 MEDAN - Sari, Lili Nur Indah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
The aim of this research are: (1) to find out the improving competence of mathematical connection and student’s creative thinking through open ended learning and usual learning, (2) to find out there was the interaction between learning and fist mathematical competence toward the improving competence mathematical connection and student’s creative thinking. This kind of research is the quasi experiment. The populations of this research are the students in eleventh grade of SMP Muhammadiyah 03 Medan. The sample chosen random sample which are VIII, as experiment class and VIII, as control class. The instrument is validated first, and the result is shown that (1) to test the competence in mathematical connection is valid with the high criteria, on other hand to test Student’s creative thinking competence is valid with the high criteria. (2) Coefficient reliability to test mathematical connection competence is 0,73 with the high category, on other hand reliability to test student’s creative thingking competence is 0,79 with the high category. Data analysis is can rid by using ANAVA two ways The result of this research Revealed that (1) there was improment competence in mathematical student’s creative thinking by using open ended learning is better than using usual learning, (2) there no interaction between learning and student’s competence level to the improment competence of mathematical connection and student’s creative thinking. The research suggests: (1) to use open ended learning as the alternative way for teachers to improve the competence in mathematical connection and student’s creative thinking. (2) learning tools is prepared well and suited with the indicator of competence and time allocation that must be reached, (3) must be selective in choosing the material of learning by using open ended learning because not all materials of teaching is suitable to apply by using open ended learning.